Sifat Fisik Dan Kimia Ikatan Pembuluh Pada Batang Kelapa Sawit (Physical and Chemical Properties of Oil Palm Trunk Vascular Bundles) - Arif Nuryawan; Affifuddin Dalimunthe; Rio Nare Saragih (FORESTA, 2012)
The research objective was to evaluate the physical and chemical properties of oil palm trunk vascular bundles. Physical properties consist of dimension, moisture content, specific gravity, and cell wall specific gravity. Chemical properties consist of extractives content, lignin content, and ash material. The evaluation methods of physical properties followed the standard which applied in wood. The evaluation methods of chemical properties followed the TAPPI standard. The information of physical and mechanical properties were shown in three section of the trunk, namely bottom, middle, and peak with average of three replication. The results of physical properties were as follow: the length of vascular bundles 10.55 cm and the diameter 0.67 mm, moisture content was 11.70%, specific gravity was 0.44, and cell wall specific gravity was 0.52. The chemical properties were solubility of cold water, hot water, NaOH 1%, lignin content, and ash material were 13.4%, 15.89%, 23.62%,22.20%, and 2,12%, respectively.Keywords : oil pump trunk vascular bundles, physical properties, chemical properties.